Tendense in die studie van die kultuur van oraliteit: Implikasies vir die verstaan van die Matteusevangelie - Nel, Celia (Hervormde teologiese studies, 1995)
Tendencies in the study of orality: Implications for the understanding of the Gospel of Matthew. The 'formgeschichtliche' method has proved to be inadequate in its conclusions on the pre-literary phase of literary documents. The study of orality provides another means of investigating the oral stages of written documents. After investigating the features of an oral culture, this article points out that ancient writers communicated nelt' information to their readers or listeners by using fomulas and themes already known to their audiences. The authors thus communicated something new to their audiences by using the already known. In this article it is argued that the Gospel of Matthew is suitable for illustrating the above principal, as the Matthean language is highly formulaic.